KEKOSONGAN NORMA PENGATURAN DATA PRIBADI PASCA KEMATIAN DAN IMPLIKASINYA TERHADAP PERTANGGUNGJAWABAN PIDANA DALAM UNDANG-UNDANG NOMOR 27 TAHUN 2022 - Ririn Kurniasi; Cristiana, Edelweisia; Alfred Yetno (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This article examines the normative gap in the regulation of personal data after the death of data subjects and its implications for criminal liability under Law Number 27 of 2022 on Personal Data Protection in Indonesia. The issue is significant due to the rapid development of digital technologies that allow personal data to persist, be processed, and potentially misused even after the data subject has died, thereby increasing legal uncertainty. However, the existing legal framework primarily regulates living data subjects and fails to explicitly address the legal status, protection mechanisms, and representation of post-mortem personal data. This study employs normative legal research using statutory, conceptual, and comparative approaches. Legal materials were collected through a systematic review of primary and secondary legal sources and analyzed qualitatively using descriptive-analytical methods. The underlying assumption of this research is that the absence of explicit regulation on post-mortem personal data weakens the enforcement of criminal liability. The findings demonstrate that this normative gap creates uncertainty in identifying victims, determining violated rights, and establishing criminal responsibility, which in turn hinders effective law enforcement and increases the risk of impunity. Comparative analysis with international practices, particularly interpretations of the General Data Protection Regulation, shows that several jurisdictions provide limited protection for post-mortem data through alternative legal mechanisms. This article emphasizes the need for explicit legal norms governing personal data after death, including regulatory options such as statutory amendment, implementing regulations, or progressive legal interpretation, as well as the recognition of heirs as representative legal subjects. These measures are essential to ensure legal certainty, justice, and effective enforcement of criminal liability in the protection of personal data.